Quyển 4 - Trần, Vân Hạc; Cà, Văn Chung (H., 2015)
Giới thiệu lịch của người Thái ở Sơn La từ năm 1974 đến năm 1998
Keywords: Văn hóa dân gian -- Lịch -- Dân tộc Thái -- Việt Nam; Lịch -- Dân tộc Thái -- Việt Nam; Dân tộc Thái -- Lịch -- Việt Nam